LOW BIRTH WEIGHT IS A RISK FACTOR OF MALNUTRITION IN CHILDREN UNDER FIVE YEARS OLD IN COASTAL AREAS - Juminten Saimin; Ahmad Fahmi Nugraha; Asmarani Asmarani; Ashaeryanto Ashaeryanto (Public Health of Indonesia)
Background: Malnutrition is a public health problem, especially in developing countries. Malnutrition of children can affect brain development during growth and increase morbidity and mortality. Low birth weight (LBW) plays an important role in child morbidity and mortality. The prevalence of malnutrition in children under five years old and LBW in Indonesia are still high.